Low Noise Amplifier with Low Power Consumption in 0.18 Micrometer CMOS Technology - Haghi, Majid; Emadi, Mohammad (International Journal of Computer Sciences and Engineering, 2019)
In this paper we present a new model of low noise amplifier and propose solutions to improve performance. Both single-head and two-head amplifiers are designed and simulated with common mode feedback circuit.